Influence of sociodemographic and economic factors on physical activity among university students - Suellem Regina Chamberllem; Márcia Gonçalves Ferreira; Paulo Rogério Melo Rodrigues; Patrícia Simone Nogueira; Rosângela Alves Pereira; Ana Paula Muraro (Universidade de Fortaleza, 2020)
Objective: To estimate the influence of socioeconomic factors on the variation of time spent by university students on the practice of physical activity after the first academic year. Methods: Longitudinal quantitative study with 348 full-time university students, between 16 and 25 years old, from capital of Mato Grosso, Brazil. Change in time spent on the practice of moderate and vigorous physical activity was evaluated in minutes per week, through the short version of IPAQ - International Physical Activity Questionnaire. The following independent variables were analyzed: sex, age, race/skin color, economic class, students' housemates and field of study. Multinomial regression analysis was used to verify the association of physical activity time variation, in tertiles, with the independent variables. Results: The overall change in median physical activity time in one year was -90.0 minutes/week, the students of higher socioeconomic status maintained the same time of practice of physical activity, while those of other classes showed a decrease in this time after the first year at university. After adjustments, the lower economic class (OR=2.85; 95%CI= 1.26-6.43) and the fact that the student lives in a house shared by students (OR=2.84; 95%CI= 1.26-6.38) were associated with reduction in time spent on physical activity. Conclusion: There was a decrease in time spent on physical activity among students from the lower economic classes who lived in a share house after the first year at university.